Unusual communication of an embedded peritoneal dialysis catheter with the colon before use: a case report with literature review - Takaya Handa; Hiroyuki Suzuki; Hiroyuki Matsubara; Hiroaki Terajima; Tatsuo Tsukamoto (Renal Replacement Therapy, 2019)
Abstract Background Bowel perforation in peritoneal dialysis (PD) is mainly caused during the perioperative period. Delayed bowel perforation is difficult to diagnose because of its heterogenous clinical signs and rarity. Previously, the methods to diagnose delayed bowel perforation were invasive, but computed tomography (CT) peritoneography is now employed as a less invasive method. There have been no literature reviews on delayed bowel perforation, including recent cases using CT peritoneography. Delayed bowel perforation before PD initiation has rarely been reported and was mostly after PD initiation. Here, we present a case and literature review of delayed bowel perforation before PD initiation possibly caused by mechanical compression of the PD catheter implanted by the Moncrief–Popovich technique. Case presentation A PD catheter was embedded in a 57-year-old woman with autosomal-dominant polycystic kidney disease, with the distal end of the PD catheter buried under the skin. She had no gastrointestinal symptoms, except renal failure progression, during conservative therapy. Nine months later, she was admitted to our hospital to exteriorize the distal end of the PD catheter. Immediately after the first PD solution was infused into her abdomen, she complained of watery diarrhea. CT peritoneography revealed an outflow of contrast media through the PD catheter into the luminal side of the sigmoid colon, suggesting an interaction between the PD catheter and the colon. Laparoscopic examination revealed that the lateral side of the PD catheter (5 cm from the catheter tip) had adhered to the sigmoid colon and that a small orifice had formed where the side hole of the catheter was attached to the colon. The lesion was entirely surrounded by fibrous tissue that prevented leakage of the intraluminal contents. After restoring the colon with a colostomy, the patient was treated with hemodialysis. Seven months later, she underwent closure of the colostomy. Conclusions Although perforation of the colon by a PD catheter through the side hole is very rare, it is important to consider the interaction of dialysis fluid with the gut if diarrhea or abdominal pain occurs after PD initiation. CT peritoneography may be helpful in identifying the bowel perforation site with minimal invasiveness.